A day 1 hCG can differentiate non-viable intrauterine pregnancy and ectopic pregnancy following endometrial curettage (Annals of Medical Research, 2021)
Aim: The aim of the present study was to determine a cutoff level for a decrease in human chorionic gonadotropin (hCG) on postoperative day 1 to confirm intrauterine pregnancy (IUP) in patients who have undergone dilatation and curettage (D/C) with a presumptive diagnosis of nonviable pregnancy of unknown location (PUL). Material and Methods: This retrospective case–control study included patients who underwent D/C with a presumptive diagnosis of failing PUL between January 2010 and June 2015. Patients with failing PUL or confirmed to have an IUP were placed in Group 1 (n=164) and patients subsequently diagnosed with ectopic pregnancy were placed in Group 2 (n=19).In all patients, serum hCG levels were obtained on the day of D/C and on the following day.Results: The decline in serum hCG percentage on day 1 after D/C was 54.2% in patients with failing PUL/abortion and 14.3% in patients with ectopic pregnancy (p0.001). A decrease in hCG of more than 35% was the most sensitive marker, with sensitivity, specificity, and positive and negative predictive values of 90%, 89%, 99%, and 50%, respectively.Conclusion: Determining post curettage day 1 hCG might aid clinicians in confirming failing IUP and in ruling out an ectopic pregnancy at an earlier date.